Contribution of spontaneous plants on the physico-chemical properties of Latosol and in the nutrition of the coffee plant (Coffea arabica L.) - Carmo, Davi Lopes; Nannetti, Dulcimara Carvalho; Dias Junior, Moacir Souza; Espiríto Santo, Djalma José; Lacerda, Tales Machado; Albuquerque, Alfredo Domingues (Coffee Science - ISSN 1984-3909, 2011)
One study was conducted on two neighboring farms in the town of Mahado, southern Minas Gerais. The aim of this work was to determine the contribution of spontaneous plants on the physicochemical properties of the Latosol and in the nutrition of the coffee plant (Coffea arabica L.). The following management systems were used: coffee crop with no spontaneous plants (CSVE/3), coffee crop with spontaneous plants (CCVE/3), both at three years old, coffee crop with spontaneous plants (CCVE/20) and banana plantation with spontaneous plants (BCVE/20), both at 20 years old, this last one being used a reference for comparisons. Undisturbed soil samples were collected for physical analysis at the depth of 0–3 and 15–18 cm, under the shadow projection of the coffee tree tops and between the rows of the banana plantation (Muse sp). Samples for soil fertility analysis were collected at the depth of 0–20 cm at the same spots of the undisturbed soil samples. Leaf samples were also taken for chemical analyses from the corresponding plants. Management with vegetative cover presented a better chemical quality of the soil with higher values of pH, base saturation, and cation exchange capacity, sum of the bases calcium and magnesium were higher. The nutrition of the coffee plant proved to better under spontaneous plant management, with higher concentrations of nitrogen, phosphorus, calcium, magnesium and sulfur in leaf tissue. The management system with no spontaneous plants showed degradation of the soil‘s physical properties with higher values of soil density and lower values of total pore volume and macroporosity.